Princess Ru and Papyrus - Stereotypes on ancient Egypt in graphic novels - Vera Vasiljević (University of Belgrade, 2016)
The decipherment of the hieroglyphic script in 1822 marked a fundamental change in the views on ancient Egypt and due to the scientific research the knowledge on the subject substantially increased ever since. Despite the wide accessibility of the results of Egyptological studies, the image of Egypt in the popular culture often contains older conceptions, and some of them, like the myth of ancient and immense wisdom, are turned into stereotypes used in certain popular media. The paper deals with their presence in graphic novels. The origins of the stereotypes are reviewed and the reasons for their persistence analysed. I argue that the sterotypes on Egypt in graphic novels became early on a codified part of the communication whithin the "comic book culture" (M. Pustz), and therefore indispensable in this medium. As representatives of different genres in the graphic novels, the series on adventures Papyrus by Lucien De Gieter, and the comic books Princess Ru by !or"e Loba#ev and Hatshepsut by Nikola Kokan Mitrović were chosen for the analysis.